Valoración de carga postural aplicando el método Reba en dos (2) empresas del sector textil de ropa interior femenina ubicadas en la comuna 4 en Santiago de Cali (Valle) en el año 2016 (2016)
The research titled assessment of postural load Reba applying the method in two (2) textile companies women's underwear located in the commune 4 in Santiago de Cali (Valley) in 2016. Its purpose is to assess the level of risk postural load using the REBA method in the two companies. The research is a kind of descriptive study, the sample is not random and involved two companies, the company with 45 employees and 1 firm 2 with 21 workers. The risk level of postural load using the REBA method in the company 1, 68% of the assessed charges has medium risk and 32% low risk. In the company 2 83% of charges has medium risk and 17% low risk.